Rovalpituzumab tesirine, a DLL3-targeted antibody-drug conjugate, in recurrent small-cell lung cancer: a first-in-human, first-in-class, open-label, phase 1 study. Issue 1 (January 2017) - Rudin, Charles M; Pietanza, M Catherine; Bauer, Todd M; Ready, Neal; Morgensztern, Daniel; Glisson, Bonnie S; Byers, Lauren A; Johnson, Melissa L; Burris, Howard A; Robert, Francisco; Han, Tae H; Bheddah, Sheila; et al.
Summary: Background: Rovalpituzumab tesirine is a first-in-class antibody-drug conjugate directed against delta-like protein 3 (DLL3), a novel target identified in tumour-initiating cells and expressed in more than 80% of patients with small-cell lung cancer. We aimed to assess the safety and activity of rovalpituzumab tesirine in patients who progressed after one or more previous regimen. Methods: We conducted a phase 1 open-label study at ten cancer centres in the USA. Eligible patients were aged 18 years or older and had histologically or cytologically confirmed small-cell lung cancer or large-cell neuroendocrine tumours with progressive measurable disease (according to Response Evaluation Criteria in Solid Tumors [RECIST], version 1.1) previously treated with one or two chemotherapeutic regimens, including a platinum-based regimen. We assigned patients to dose-escalation or expansion cohorts, ranging from 0·05 mg/kg to 0·8 mg/kg rovalpituzumab tesirine intravenously every 3 weeks or every 6 weeks, followed by investigation of the dose schedules 0·3 mg/kg and 0·4 mg/kg every 6 weeks and 0·2 mg/kg every 3 weeks. Primary objectives were to assess the safety of rovalpituzumab tesirine, including the maximum tolerated dose and dose-limiting toxic effects. The primary activity endpoint was objective response by intention-to-treat analysis. This study is registered withClinicalTrials.gov, numberNCT01901653 . The study is closed to enrolment; this report focuses on the cohort with small-cell lung cancer. Findings: Between July 22, 2013, and Aug 10, 2015, 82 patients were enrolled, including 74 patients with small-cell lung cancer and eight with large-cell neuroendocrine carcinoma, all of whom received at least one dose of rovalpituzumab tesirine. Dose-limiting toxic effects of rovalpituzumab tesirine occurred at a dose of 0·8 mg/kg every 3 weeks, including grade 4 thrombocytopenia (in two of two patients at that dose level) and grade 4 liver function test abnormalities (in one patient). The most frequent grade 3 or worse treatment-related adverse events in 74 patients with small-cell lung cancer were thrombocytopenia (eight [11%]), pleural effusion (six [8%]), and increased lipase (five [7%]). Drug-related serious adverse events occurred in 28 (38%) of 74 patients. The maximum tolerated dose of rovalpituzumab tesirine was 0·4 mg/kg every 3 weeks; the recommended phase 2 dose and schedule is 0·3 mg/kg every 6 weeks. At active doses of rovalpituzumab tesirine (0·2 mg/kg or 0·4 mg/kg every 3 weeks or 0·3 mg/kg or 0·4 mg/kg every 6 weeks), 11 (18%) of 60 assessable patients had a confirmed objective response. 11 (18%) of 60 assessable patients had a confirmed objective response, including ten (38%) of 26 patients confirmed to have high DLL3 expression (expression in 50% or more of tumour cells). Interpretation: Rovalpituzumab tesirine shows encouraging single-agent antitumour activity with a manageable safety profile. Further development of rovalpituzumab tesirine in DLL3-expressing malignant diseases is warranted. Funding: Stemcentrx Inc.